2022
DOI: 10.55730/1300-0144.5345
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of anakinra compared to standard care of treatment for COVID-19: a metaanalysis

Abstract: Background/aim As SARS-CoV-2 continues to spread worldwide, this study brings to light the link that anakinra, a recombinant IL-1 receptor antagonist, has in averting grave clinical outcomes. The objectives of this meta-analysis are to investigate the effects of anakinra in interventional groups compared to control/standard of care groups on mortality along with the provision of a prevalence estimate of the variables associated with death (C-reactive protein-CRP, ferritin, acute respiratory distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Poprzez konkurencyjne hamowanie wiązania cytokin z antagonistami receptora interleukiny, anakinra ma potencjał, by kontrolować aktywny stan zapalny i przerwać pętlę autozapalną [30,39]. Dostępne dowody wskazują, że leczenie takie zmniejsza zarówno potrzebę inwazyjnej wentylacji mechanicznej, jak i ryzyko zgonu hospitalizowanych niezaintubowanych pacjentów z COVID-19 bez zwiększania ryzyka zdarzeń niepożądanych [35,36]. W innych próbach, biorących pod uwagę 1297 oraz 2032 badanych, zauważono, że średnie wartości ferrytyny jako parametru zapalnego w surowicy oraz D-dimery uległy obniżeniu.…”
Section: Rola Interleukinyunclassified
“…Poprzez konkurencyjne hamowanie wiązania cytokin z antagonistami receptora interleukiny, anakinra ma potencjał, by kontrolować aktywny stan zapalny i przerwać pętlę autozapalną [30,39]. Dostępne dowody wskazują, że leczenie takie zmniejsza zarówno potrzebę inwazyjnej wentylacji mechanicznej, jak i ryzyko zgonu hospitalizowanych niezaintubowanych pacjentów z COVID-19 bez zwiększania ryzyka zdarzeń niepożądanych [35,36]. W innych próbach, biorących pod uwagę 1297 oraz 2032 badanych, zauważono, że średnie wartości ferrytyny jako parametru zapalnego w surowicy oraz D-dimery uległy obniżeniu.…”
Section: Rola Interleukinyunclassified
“…However, such observational findings required extensive assessments in well-conducted randomized clinical trials to verify the reported outcomes ( Cavalli et al, 2020 ; Langer-Gould et al, 2020 ). Later, few small randomized trials and meta-analyses were conducted to assess the benefit of anakinra in COVID-19 patients with inconclusive outcomes ( Balkhair et al, 2021 ; Barkas et al, 2021 ; Declercq et al, 2021 ; Audemard-Verger et al, 2022 ; Kharazmi et al, 2022 ; Malık et al, 2022 ; Naveed et al, 2022 ). As in selected patients with severe COVID-19 pneumonia, anakinra has demonstrated beneficial outcomes, while it did not show a significant benefit in other patient groups ( Balkhair et al, 2021 ; Barkas et al, 2021 ; Declercq et al, 2021 ; Audemard-Verger et al, 2022 ; Kharazmi et al, 2022 ; Malık et al, 2022 ; Naveed et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Later, few small randomized trials and meta-analyses were conducted to assess the benefit of anakinra in COVID-19 patients with inconclusive outcomes ( Balkhair et al, 2021 ; Barkas et al, 2021 ; Declercq et al, 2021 ; Audemard-Verger et al, 2022 ; Kharazmi et al, 2022 ; Malık et al, 2022 ; Naveed et al, 2022 ). As in selected patients with severe COVID-19 pneumonia, anakinra has demonstrated beneficial outcomes, while it did not show a significant benefit in other patient groups ( Balkhair et al, 2021 ; Barkas et al, 2021 ; Declercq et al, 2021 ; Audemard-Verger et al, 2022 ; Kharazmi et al, 2022 ; Malık et al, 2022 ; Naveed et al, 2022 ). The presented open-label randomized clinical trial aimed to explore the safety and efficacy of anakinra in addition to standard of care (SOC) compared to SOC alone in patients with confirmed COVID-19 infection with respiratory distress and evidence of cytokine release syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The first reported randomized control trial was terminated early for concerns that anakinra was not improving outcomes in patients with mild-to-moderate COVID-19 pneumonia [ 21 ]. Two meta-analyses suggested a COVID-19 survival benefit of anakinra, also among those patients with signs of hyperinflammation [ 22 ] and in the absence of glucocorticoid co-administration [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%